Corporate Governance and Audit Report Lag in Malaysia - Mohamad Naimi Mohamad-Nor; Rohami Shafie; Wan Nordin Wan-Hussin (Asian Academy of Management Journal of Accounting and Finance, 2010)
This paper examines audit report lag in Malaysian public listed companies, following the implementation of the Malaysian Code on Corporate Governance in 2001. It departs from the standard audit report lag studies by incorporating characteristics of the board of directors and the audit committee. Multivariate analysis using 628 annual reports for the year ended 2002 indicates that active and larger audit committees shorten audit lag. However, we fail to find evidence that audit committee independence and expertise are associated with the timeliness of the audit report.